Therapeutic intervention based on circulating tumor cell phenotype in metastatic breast cancer: concept of the DETECT study program - De Gregorio, Amelie; Friedl, Thomas W. P.; Schochter, Fabienne; Scholz, Christoph; de Gregorio, Nikolaus; Huober, Jens; Rack, Brigitte; Trapp, Elisabeth; Alunni-Fabbroni, Marianna; Müller, Volkmar; Schneeweiss, Andreas; Pantel, Klaus; et al. (Archives of gynecology and obstetrics, 2016)
The aim of the ongoing DETECT study program is to evaluate therapeutic intervention based on phenotypes of circulating tumor cells (CTC) in patients with metastatic breast cancer (MBC). Currently (as of July 2015) more than half of the projected about 2000 patients with MBC have already been screened for CTC.
Published online: 9 September 2015
Gesehen am 22.05.2020